Perbedaan Kualitas Hidup Lansia yang Aktif Mengikuti Posyandu Lansia dengan yang Tidak Aktif Mengikuti Posyandu Lansia di Kelurahan - Salestin Rambu Malairu; Joko Pitoyo (PROFESSIONAL HEALTH JOURNAL, 2020)
Problems often faced by eldery is decreasing ability is like physical health, or decrease ability to socialize with others. Health Service Centre is one of activities aimed to elderly to get health services easily.Objective aim to know differences from quality of life of active elderly with inactive elderly on follow health service centre in Mojolangu Village Of Lowokwaru District, method is design research is used a Cross Sectional design. Sample are 40 elderly, taking sample is using purposive sampling. Samples divided to 2, that is 20 elderly who are active, and 20 elderly who are inactive Data analysis is using Chi Square test. The results showed there are 5 (25%) respondents who are actively follow elderly Health Service Centre had a good quality of life, while 1 (5%) respondents who are inactively follow elderly Health Service Centre had a good quality of life. Respondents with a good quality of life average attendance participed in elderly Health Service Centre by 7 times, while inactive elderly as much as 3/4 times. Chi Square test results obtained by the value of p = 0,002, so concluded there is a differences from quality of life of active elderly with inactive elderly on follow health service centre in Mojolangu Village of Lowokwaru. Suggestion from this study are further researchers can use this research and more developed. Keywords: Quality of Life, Elderly, Health Service Centre